Double aortic arch: a comparison of fetal cardiovascular magnetic resonance, postnatal computed tomography and surgical findings - van Poppel, Milou P.M.; Lloyd, David F.A.; Steinweg, Johannes K.; Mathur, Sujeev; Wong, James; Zidere, Vita; Speggiorin, Simone; Jogeesvaran, Haran; Razavi, Reza; Simpson, John M.; Pushparajah, Kuberan; Vigneswaran, Trisha V. (Journal of cardiovascular magnetic resonance, 2024)
In double aortic arch (DAA), one of the arches can demonstrate atretic portions postnatally, leading to diagnostic uncertainty due to overlap with isolated right aortic arch (RAA) variants. The main objective of this study is to demonstrate the morphological evolution of different DAA phenotypes from prenatal to postnatal life using three-dimensional (3D) fetal cardiac magnetic resonance (CMR) imaging and postnatal computed tomography (CT)/CMR imaging. Three-dimensional fetal CMR was undertaken in fetuses with suspected DAA over a 6-year period (January 2016–January 2022). All cases with surgical confirmation of DAA were retrospectively studied and morphology on fetal CMR was compared to postnatal CT/CMR and surgical findings. Thirty-four fetuses with surgically confirmed DAA underwent fetal CMR. The RAA was dominant in 32/34 (94%). Postnatal CT/CMR was undertaken at a median age of 3.3 months (interquartile range 2.0–3.9) demonstrating DAA with patency of both arches in 10/34 (29%), with 7 showing signs of coarctation of the left aortic arch (LAA). The LAA isthmus was not present on CT/CMR in 22/34 (65%), and the transverse arch between left carotid and left subclavian artery was not present in 2 cases. Fetal CMR provides novel insights into perinatal evolution of DAA. The smaller LAA can develop coarctation or atresia related to postnatal constriction of the arterial duct, making diagnosis of DAA challenging with contrast-enhanced CT/CMR. This highlights the potentially important role for prenatal 3D vascular imaging and might improve the interpretation of postnatal imaging. [Display omitted]